Titin-based Nanoparticle Tension Sensors Map High-Magnitude Integrin Forces within Focal Adhesions - Galior, Kornelia (Nano Lett, 2015)
Mechanical forces transmitted through integrin transmembrane receptors play important roles in a variety of cellular processes ranging from cell development to tumorigenesis. Despite the importance of mechanics in integrin function, the magnitude of integrin forces within adhesions remains unclear. Literature suggests a range from 1 to 50 pN, but the upper limit of integrin forces remains unknown. Herein we challenge integrins with the most mechanically stable molecular tension probe, which is comprised of the immunoglobulin 27th (I27) domain of cardiac titin flanked with a fluorophore and gold nanoparticle. Cell experiments show that integrin forces unfold the I27 domain, suggesting that integrin forces exceed 80 pN. The introduction of a disulfide bridge within I27 “clamps” the probe and resists mechanical unfolding. Importantly, the addition of a reducing agent initiates SH exchange, thus unclamping I27 at a rate that is dependent on the applied force. By recording the rate of S-S reduction in clamped I27 we infer that integrins apply 110+/−15 pN within focal adhesions. The rates of S-S exchange are heterogeneous and integrin subtype-dependent. Nanoparticle titin tension sensors along with kinetic analysis of unfolding demonstrate that a subset of integrins apply tension many fold greater than previously reported.